Information System for Internship and Final Project Management Based on Laravel Framework - Yudhi Prabowo Kusuma; Sutrisno Sutrisno; Muhammad Hamka Ibrahim (Journal of Electrical, Electronic, Information, and Communication Technology, 2020)
The Development of Portal Elektro Information System is carried out to create solutions for administrative problems related to Internship and Final Project, especially students, lecturers, and Electrical Engineering staff. Moreover it is an effort to improve the quality of the system to be more innovative and support the needs of Electrical Engineering study program. The System of Portal Elektro covers student needs to carry out internship or final project, starting from implementation guidelines, proposal writing, until becomes final report. This information system is developed with Rapid Application Development method, and use Laravel framework with the concept of MVC (Model, View, Controller) which can separate application based on application components, such as: manipulation data, controller, and user interface. With the RAD method and Laravel framework, application development can be done quickly and structured making it easier for further development in the future. The developed system has been successfully tested and applied in the Electrical Engineering study program at UNS and is planned to be implemented in several other study programs.